DYNAMIC PROJECTION OF CLIMATE CHANGE SCENARIOS ON TROPICAL TREES' ABOVEGROUND CARBON STORAGE IN WEST PAPUA - Maulana, Sandhi Imam; Wibisono, Yohannes (Association of Indonesian Forestry and Environment Researchers and Technicians, 2017)
Through photosynthetic activities, tropical forest ecosystems capture and store the most significant carbon emissions in the form of biomass compared with other types of vegetation, and thus play a highly crucial part in dealing with climate change. However, such important role of tropical forest is very fragile from extreme changes in temperature and precipitation, because carbon storage in forest landscape is strongly related to those climate variables. This paper examines the impacts of future climate disturbances on aboveground carbon storage of three tropical tree species, namely Myristica sp., Palaquium sp., and Syzygium sp. through “what if ” scenarios evaluation using Structural Thinking and Experimental Learning Laboratory with Animation (STELLA). Results highlighted that when the dynamic simulation was running with five IPCC’s climate change scenarios (Constant year 2000 concentrations, B1, A1T, A2, and A1F1) for 200 years simulation period, then moderate climate change scenarios occured, such as B1 and A1T, would have already caused significant statistical deviation to all of those tree species. At the worst level of A1F1, the 4°C temperature was coupled with 20% reduction in precipitation. Palaquium sp. showed the highest reduction of aboveground carbon storage with about 17.216% below its normal value. This finding implies the negative climate feedbacks should be considered seriously to ensure the accuracy of long term forest carbon accounting under future climate uncertainty.